Droplets deposition and harvest-aid efficacy for UAV application in arid cotton areas in Xinjiang, China - Wang, Guobin; Wang, Jiahui; Chen, Pengchao; Han, Xiaoqiang; Chen, Shengde; Lan, Yubin (International Journal of Agricultural and Biological Engineering, 2022)
With the development of Unmanned Aerial Vehicle (UAV) sprayers, the application of low-volume spraying of harvest-aid and other agrochemicals to cotton using UAVs is becoming a new agronomic trend worldwide. The effect of spray volume and canopy density for UAV spraying is significant but was rarely studied. In this study, five representative spray volumes were explored to examine the effect of spray volume on deposition and harvest-aid efficacy for cotton using a UAV sprayer. To explore the effect of canopy density, similar tests were carried out in a field located nearby with a lower leaf area index (LAI). A conventional trailer boom sprayer was selected for comparison. Different spray volumes had a significant effect on defoliation, but had no significant effect on boll opening and fiber quality. A higher defoliation rate was achieved in the lower LAI field. The total rate of defoliation using the UAV was inferior to the boom sprayer in the high LAI field for lower deposition and defoliation rate in the lower canopy. Considering the deposition, defoliation rate, and working efficiency, a spray volume of 15.0 L/hm2 with an average droplet size of 150 μm is recommended for UAV application.Keywords: UAV, droplets deposition, spray volume, canopy density, leaf area index, defoliation, boll opening rateDOI: 10.25165/j.ijabe.20221505.6425Citation: Wang G B, Wang J H, Chen P C, Han X Q, Chen S D, Lan Y B. Droplets deposition and harvest-aid efficacy for UAV application in arid cotton areas in Xinjiang, China. Int J Agric & Biol Eng, 2022; 15(5): 9–18.